SOLUSI PENINGKATAN GREEN PURCHASE INTENTION MELALUI ENVIRONMENTAL KNOWLEDGE - Sri Rahayu (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2020)
The purpose of this study is to find a solution to the research gap between green advertising and green purchase intention, by proposing environmental knowledge as a mediating variable. Based on previous studies, green advertising is believed to increase consumer knowledge about environmentally friendly products. In addition, environmental knowledge plays an important role in increasing green purchasing intentions. It shows that green advertising has a direct and indirect influence through the environment knowledge. Therefore this study seeks to build a conceptual model that is expected to contribute to academics and managerial practice. For academics, the conceptual model is expected to be empirically tested through field research. Whereas for green marketing management practices, the conceptual model can be used as a reference in an effort to increase consumer purchase intentions.